2018
DOI: 10.5530/jyp.2018.10.21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Over-the-Counter Analgesics Usage among Patients attending Primary Health Care Centers in Jeddah, Saudi Arabia

Abstract: Objective: To estimate the prevalence and describe the pattern of OTC use among patients attending primary healthcare (PHC) centers, and to assess their knowledge and attitude regarding the related side effects. Method: A cross-sectional study was carried out among 400 adult patients attending the General Medicine clinic in 10 selected PHC centers in Jeddah, Saudi Arabia. The data collected included socioeconomic parameters, practice and pattern of OTC analgesics use in past 6 months, knowledge and attitude ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 23 publications
2
22
1
Order By: Relevance
“…18 In Saudi people also, the most common indication for analgesic was headache. In Jeddah, the next common indication was arthralgia whereas menstrual pain was the second most common indication as found in study done by Karami et al 6,12 About 43.18% of girls were using these analgesics for menstrual pain. Probably they know that for dysmenorrhea these NSAIDS are very effective drugs.…”
Section: Reported To Physicianmentioning
confidence: 94%
See 3 more Smart Citations
“…18 In Saudi people also, the most common indication for analgesic was headache. In Jeddah, the next common indication was arthralgia whereas menstrual pain was the second most common indication as found in study done by Karami et al 6,12 About 43.18% of girls were using these analgesics for menstrual pain. Probably they know that for dysmenorrhea these NSAIDS are very effective drugs.…”
Section: Reported To Physicianmentioning
confidence: 94%
“…Regarding reason for self medication, our finding is similar to findings in Bangladesh, Saudi Arabia, Madhya Pradesh and Nellore, India. 2,6,11,14 One study done in Pokhara, Nepal showed that the most common reason for self medication was -it is time saving (45.5%). 1 This data is very low in our study (6.21%).…”
Section: Reported To Physicianmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they were lacking the concept of safe usage of OTC drugs. Studies conducted in Saudi Arabia indicated that 58.1% of participants did not know the side effects of analgesics and most people lack knowledge about the appropriate dose of them [11,12]. A work done by the Academic Pediatrics in the USA to evaluate and compare knowledge and literacy of OTC medications among middle and high students illustrated that only 8% of the students responded correctly to side effects questions compared to 67% did not know [13].…”
Section: Introductionmentioning
confidence: 99%